Evaluation of the Possible Benefits of Breast Cancer Screening in Women Aged 40 to 49 Years in the Steel Valley Region, Brazil: Early Breast Cancer Test - Aires Lima, Cátia Cilene; Daruich de Souza, Carla (Archives of Breast Cancer, 2024)
Background: This study investigates the effectiveness of mammographic screening for women aged 40 to 49 in Brazil's Steel Valley Region. Despite a Ministry of Health recommendation to start screenings at 50, 25% of breast cancer cases occur in the 40-49 age group. Methods: The retrospective analysis, spanning 2008-2019 at Marcio Cunha Hospital, compared two groups: cancer diagnosed via screening mammography (277) and diagnostic mammography (229). Results: Results showed delayed diagnoses for non-screened women, with 4.16 times higher mortality rate. Screening facilitated earlier detection of less malignant cancers (85.9% vs. 43.7%). Women diagnosed through screening were more likely to preserve their breasts (28.9% vs. 55.5% for Radical Breast Surgery and 71.1% vs. 28.9% for Breast-Sparing Surgery), and fewer axillary lymphadenectomies were performed. All statistical tests performed returned a p-value lower than 0.05 showing high statistical significance. Conclusion: The findings support extending screening mammography access to all women over 40 in the Steel Valley region and underscore the need for broader-scale research in other areas. Recommendations include enhancing public awareness and establishing a breast cancer surveillance service.